Aplicação de fósforo e potássio na implantação de Corymbia citriodora (Hook.) K. D. Hill & L. A. S. Johnson - Biagiotti, Gabriel [UNESP] (2015)
The forest fertilization at implementation can promote early growth and the establishment of trees in a reforestation. Corymbia citriodora is one of the most timber species planted in Brazil for several commercial purposes. Experiments were conducted under field conditions in order to verify the effects of phosphorus and potassium on growth, nutrient concentration of leaves, and production of C. citriodora wood biomass at the implementation phase. At the phosphorus experiment 0, 10, 20, 30, 40, and 50 kg ha-1 of P2O5 were applied at planting and at the potassium experiment 0, 30, 60, 90, 120, and 150 kg ha-1 of K2O were applied in three times: planting, 3 and 6 months of age. The experiments were performed in Argissolo Vermelho Amarelo (Ultisol). The seedlings were planted in 3 x 2 m spacing. The experimental design was the randomized block, with six treatments and four replications. The results indicated that after a year of implementation, the application of 30 kg ha-1 of P2O5 promoted greater plant growth and it increased the wood biomass production, allowing a wood increase of 65% when compared to the control. In the potassium experiment, the application of 90 kg ha-1 of K2O promoted an increase of 75% in wood production in the first year